The European archaeologist. - Cleere, Henry,; Waugh, Karen,; Samson, Ross, (Archaeopress, 2014)
This volume gathers together the first 10 years of 'The European Archaeologist', from Winter 1993 through to the 10th Anniversary Conference Issue, published in 2004 for the Lyon Annual Meeting.